Rice Germplasm, Genetics and Improvement - Yan, Wengui; Bao, Jinsong (IntechOpen, 2014)
Rice is a staple food for half of the worlds population mostly in Asia. Productivity of rice has largely been improved since the Green Revolution in 1960s. Further improvement of rice yield is necessary to keep pace with population growth, which is a challenging task for breeders. This book, Rice - Germplasm, Genetics and Improvement, as its name implies, comprehensively reviews current knowledge in germplasm exploration, genetic basis of complex traits, and molecular breeding strategies in rice. In the germplasm part, we highlight the application of wild rice in rice breeding. In the genetics part, most of the complex traits related with yield, disease, quality have been covered. In the improvement part, Chinese experiences in hybrid rice breeding have been summarized together with many molecular breeding practices scattering in different chapters.